1998
DOI: 10.1002/1529-0131(199809)41:9<1591::aid-art9>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of the safety and efficacy of SC-58635, a novel cyclooxygenase 2 inhibitor: Efficacy and safety in two placebo-controlled trials in osteoarthritis and rheumatoid arthritis, and studies of gastrointestinal and platelet effects

Abstract: Objective. To investigate the efficacy and safety of , an antiinflammatory and analgesic agent that acts by selective cyclooxygenase 2 (COX-2) inhibition and is not expected to cause the typical gastrointestinal (GI), renal, and platelet-related side effects associated with inhibition of the COX-1 enzyme.Methods. Four phase I1 trials were performed a 2-week osteoarthritis efficacy trial, a 4-week rheumatoid arthritis efficacy trial, a l-week endoscopic study of GI mucosal effects, and a l-week study of effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
177
0
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 445 publications
(191 citation statements)
references
References 43 publications
(2 reference statements)
6
177
0
8
Order By: Relevance
“…CXB is highly effective in the treatment of osteoarthritis and rheumatoid arthritis when compared to other NSAIDS, for example Naproxen and Diclofenac 5,6 . CXB is also used to treat pain and inflammation associated with ankylosing spondylitis, as well as to treat menstrual cramps and colonic polyps 1 .…”
Section: Introductionsupporting
confidence: 88%
“…CXB is highly effective in the treatment of osteoarthritis and rheumatoid arthritis when compared to other NSAIDS, for example Naproxen and Diclofenac 5,6 . CXB is also used to treat pain and inflammation associated with ankylosing spondylitis, as well as to treat menstrual cramps and colonic polyps 1 .…”
Section: Introductionsupporting
confidence: 88%
“…The clinical benefits of nonsteroidal anti-inflammatory drugs imply an exacerbating role for cyclooxygenase-mediated PG production in the pathogenesis of RA (11). Previous experimental evidence suggested that the major PGs, PGE 2 and PGI 2 , are abundantly produced in arthritic joints, and they aggravate arthritis by activating immune responses (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high concentrations of PGs are detected in the synovial fluid of RA patients (10). Treatment with nonsteroidal anti-inflammatory drugs inhibits cyclooxygenasedependent PG production, ameliorating the manifestations of RA (11). Using genetically modified mice, Honda et al (12) and McCoy et al (13) demonstrated that activation of the PGE 2 -E prostanoid2/4 or PGI 2 -I prostanoid signaling pathway exacerbated collagen-induced murine arthritis.…”
mentioning
confidence: 99%
“…These actions are believed to be caused by COX-1 inhibition (Williams and DuBois, 1996); therefore, selective inhibition of inducible COX-2 would provide more specific and beneficial anti-inflammatory and analgesic effects Seibert et al, 1994). Accordingly, all selective COX-2 inhibitors cause significantly less gastrointestinal toxicity than general NSAIDs (Simon et al, 1998), and its anti-inflammatory and analgesic efficacies are comparable with that of nonselective NSAIDs such as naproxen and diclofenac (Maini et al, 1999). There is some controversy about the COX-2-independent effects of NSAIDs.…”
Section: Discussionmentioning
confidence: 99%